PENGENDALIAN PERSEDIAAN PADA PERUSAHAAN AIR MINUM PT. BANDANGAN TIRTA AGUNG, PT. PANEN EMBUN KEMAKMURAN, DAN PT. MANDRAGUNA ADITAMA DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) - Eni Suasri (Jurnal Riset Akuntansi Politala, 2023)
This study aims to determine the optimal frequency of purchasing raw materials for Cup 220 ml and Straw using the Economic Order Quantity (EOQ) method at PT. Bandangantirta Agung, PT. Harvest Dew Prosperity and PT. Mandrapurna Aditama. The type of data used is quantitative data, with qualitative research methods. The results obtained for the frequency of purchases from the three companies, PT Panen Embun Kemakmuran which get optimal results compared to other companies with a frequency of 3 times for Cup 220 and 8 times for straw based on the calculation of the EOQ method. Meanwhile, based on the Company's policy 9 times and 8 times the frequency of purchases made.